(untitled) (Acta Scientiarum. Biological Sciences, 2024)
Wheat is one of the most significant crops commercially because of its growing use. There is a real concern about the safety of grain that has been stored for a long time on a worldwide scale in order to get and retain a supply of high-quality grains. There are numerous methods to store wheat, however, traditional techniques are still used in Algeria. During storage, wheat grains are infested with pests and diverse microbial populations that can cause grain loses and disease. Preharvest, harvest, transportation, storage, and processing are all potential sources of microbial contamination in wheat. Fungi are the most contaminating flora, presenting mycotoxin excretion risk. Whereas lactic acid bacteria represent the fermentation flora. Contrary to what some research has found regarding the decrease in the nutritional value of wheat during storage, the storage in underground pits can enhance the product’s nutritional quality. Durum wheat fermentation is primarily a crucial technique that, when done on an industrial scale, might produce new products with improved technological and nutritional qualities. This present review highlights the storage methods available worldwide, different losses of wheat during storage, the effects of the storage conditions and natural fermentation on the quality of the stored wheat.